Quality of Life in Women with Congenital Disorders of Reproductive Organs After Surgery - Ika Arfita; Nuring Pangastuti†; Shinta Prawitasari; Sumarni Sumarni (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2026)
Background: Female reproductive organs' congenital abnormalities consist of abnormalities in the hymen, vagina, cervix, uterus, and others1. These abnormalities can affect women's ability to menstruate, sexual relations, reproduction, and psychological conditions2. Management of this abnormality depends on the defects of the organs involved and the expected improvement in function. This research was conducted because of the limitation of these cases.Objective: This study aims to determine the quality of life after surgery in women with congenital abnormalities of the reproductive organs.Methods: This study used a prospective study with a descriptive observational cross-sectional method. The population was patients at the Obstetrics Gynecology Polyclinic of Dr. Sardjito Hospital Yogyakarta in 2022 who had congenital disorders of the reproductive organs, aged at least 17 years old, and had undergone surgery. Participants filled out the FSFI and sociodemographic questionnaire.Results: There were 15 participants with 3 types of congenital abnormalities, namely 2 hymenal disorders (microperforate hymen and cribiform hymen), 9 vaginal abnormalities (vaginal agenesis and cervicovaginal agenesis), and 4 uterine and vaginal abnormalities (HWW syndrome). After surgery, 13 people experienced an improvement in abdominal pain; 9 people with primary amenorrhoea were able to menstruate; and 8 married people were able to have sex after surgery. For sexual function, 62.5% of participants had good FSFI scores.Conclusion: Surgery can provide a good function for abdominal pain, menstruation, and sexual relations.